Frequency & pattern of malignancy in solitary thyroid nodule (Bangladesh Journal of Otorhinolaryngology, 2010)
This cross sectional study done in the department of Banghabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital during the period of July 2005 to October 2007 to determine frequency & pattern of malignancy in solitary thyroid nodule. For this study, 118 patients who were diagnosed as a case of malignancy in solitary thyroid nodule by detailed history, clinical examination, thyroid hormone assay, ultrasonogram, thyroid scan, FNAC and histopathological examination, were collected. In this study majority of the patients were within 21-40 years of age. Frequency of solitary thyroid nodule is more in female with male female ratio 1: 2.11 Majority of the nodules were firm (72.03%), others were hard (16.95%) and cystic (11.02%). Malignant lesion was more common in hard nodule (70%). Most of the nodules were cold (66.10%) among them 25.6% cases were malignant, followed by warm (30.5%) and hot (3.3%). No malignancy was found in hot nodule. FNAC showed colloid nodule (44%), cellular follicular lesion (29.66%), papillary carcinoma (12.7%), colloid degeneration (4.2%) and medullary carcinoma (1.6%) Out of 118 patients, histopathologically non malignant were 96 (81.35%) and malignant were 22(18.65%). Among malignant cases, 16 (72.72%) cases were papillary carcinoma, 4 (18.18%) cases were follicular carcinoma and 2(9.1%) cases were medullary carcinoma. Key words: Solitary thyroid nodule, FNAC, Papillary carcinoma, Follicular carcinomaDOI: 10.3329/bjo.v15i1.4303 Bangladesh J of Otorhinolaryngology 2009; 15(1): 1-5